2020
DOI: 10.1136/flgastro-2019-101371
|View full text |Cite
|
Sign up to set email alerts
|

IBD in pregnancy: recent advances, practical management

Abstract: Inflammatory bowel disease (IBD) poses complex issues in pregnancy, but with high-quality care excellent pregnancy outcomes are achievable. In this article, we review the current evidence and recommendations for pregnant women with IBD and aim to provide guidance for clinicians involved in their care. Many women with IBD have poor knowledge about pregnancy-related issues and a substantial minority remains voluntarily childless. Active IBD is associated with an increased risk of preterm birth, low for gestation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 115 publications
0
40
0
3
Order By: Relevance
“…Table 1 shows separately the outcomes of pregnancies from clinical trials and postmarketing studies reported in other publications until February, 2020 (Clowse et al, 2016;Mahadevan et al, 2018;Mahadevan et al, 2020). A fact of considerable importance about these results is that a group of 13 patients in rheumatoid arthritis clinical trials received concomitant treatment with methotrexate, a known teratogenic drug (Selinger et al, 2020;Verberne, de Haan, van Tintelen, Lindhout, & van Haelst, 2019). This could have influenced the outcomes as a confounding factor, although its impact was not assessed (Clowse et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Table 1 shows separately the outcomes of pregnancies from clinical trials and postmarketing studies reported in other publications until February, 2020 (Clowse et al, 2016;Mahadevan et al, 2018;Mahadevan et al, 2020). A fact of considerable importance about these results is that a group of 13 patients in rheumatoid arthritis clinical trials received concomitant treatment with methotrexate, a known teratogenic drug (Selinger et al, 2020;Verberne, de Haan, van Tintelen, Lindhout, & van Haelst, 2019). This could have influenced the outcomes as a confounding factor, although its impact was not assessed (Clowse et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to expert opinion and the European League Against Rheumatism (EULAR) guidelines, therapy with tofacitinib should be discontinued between 4 and 8 weeks before conception when possible (Förger & Villiger, 2016;Giles et al, 2019;Gisbert & Chaparro, 2020;Götestam Skorpen et al, 2016;Puchner et al, 2019;Richez et al, 2019;Selinger et al, 2020). Although tofacitinib has a half-life of approximately 3 hr in plasma (Dowty et al, 2014;Pfizer Inc, 2019;Richez et al, 2019), this longer window is needed due to the persistence of its pharmacodynamic effects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It can also be used as a marker of disease activity in established IBD. However, studies assessing the value of calprotectin during pregnancy are conflicting [5][6][7] and results therefore need to be interpreted only with correlation within the clinical context. Faecal immunochemical testing (FIT), which detects minute amounts of blood in the stool, is increasingly being used in primary care to screen for bowel cancer.…”
Section: Assessmentmentioning
confidence: 99%
“…The management of inflammatory bowel disease (IBD) in pregnancy involves a delicate balance between maintaining optimal maternal health while avoiding harm to the foetus 1,2 . Poor disease control is associated with negative outcomes including small for gestational age and low birth weight (LBW).…”
mentioning
confidence: 99%